2007
DOI: 10.1007/s10824-007-9045-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cultural values: developing an attitudinal scale

Abstract: Attitude-behaviour, Cultural worldview scale, Scale development, Factor analysis, Population segmentation, Nonmarket valuation, Z11,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 35 publications
3
34
1
3
Order By: Relevance
“…As to the structure of the CW scale, Choi et al [18] identified nineteen items that showed four underlying factors: perceived connectedness between people of different generations and different cultural backgrounds (F1; LINKAGES), recognition of diverse cultural values (F2; RECOGNITION), awareness of cultural loss (F3; LOSS), and preservation of traditions and customs (F4; TRADITIONS). When Choi et al [18] tested this scale with two Australian samples with partially different items, the four-dimensional structure was reasonably stable and reliable, with Cronbach's alpha (showing internal consistency) values ranging between 0.69 and 0.83 for the four sub-scales.…”
Section: Attitudinal Variables and Choice Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…As to the structure of the CW scale, Choi et al [18] identified nineteen items that showed four underlying factors: perceived connectedness between people of different generations and different cultural backgrounds (F1; LINKAGES), recognition of diverse cultural values (F2; RECOGNITION), awareness of cultural loss (F3; LOSS), and preservation of traditions and customs (F4; TRADITIONS). When Choi et al [18] tested this scale with two Australian samples with partially different items, the four-dimensional structure was reasonably stable and reliable, with Cronbach's alpha (showing internal consistency) values ranging between 0.69 and 0.83 for the four sub-scales.…”
Section: Attitudinal Variables and Choice Modelsmentioning
confidence: 99%
“…When Choi et al [18] tested this scale with two Australian samples with partially different items, the four-dimensional structure was reasonably stable and reliable, with Cronbach's alpha (showing internal consistency) values ranging between 0.69 and 0.83 for the four sub-scales. Research has also demonstrated the content validity, predictive validity, and construct validity of the CW scale, although, there is some suggestion that the cultural loss sub-scale (F3) may not contribute to the overall explanatory power of the scale as much as the other factors [18]. Choi et al [18] proposed a combined version, which has not been empirically tested as a single scale, with the nineteen items slightly modified from those used in the two case studies (see Table 3).…”
Section: Attitudinal Variables and Choice Modelsmentioning
confidence: 99%
See 3 more Smart Citations